PENGARUH HEALTH EDUCATION TERHADAP TINGKAT PENGETAHUN PADA PASIEN HIPERTENSI: Literature Review - Hadi Kusuma Atmaja; Erien Luthfia (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Background: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg at two measurements with an interval of five minutes in a fairly healthy or calm condition. This study aims to determine the effect of health education on the level of knowledge in hypertensive patients.Methods: This study used the Literature method with journal search using Google Scholar to determine journals according to the inclusion and exclusion criteria and then reviewed. Based on a review of 5 journals found, the research method was obtained using pre-experimental research with a pretest-posttest one group design, the sampling technique with purposive sampling supported by 30-65 respondents, analyzed by the Wilcoxon test.Results: Based on the 5 journals that were conducted, the literature review concluded that there was an effect of health education on the level of knowledge in hypertensive patients.Conclusions and suggestions: Based on the results of the journal analysis obtained from the research that there is an effect of health education on the knowledge level of hypertensive patients. It is hoped that respondents who can apply the knowledge issued to reduce the suffering of hypertension.